EKSISTENSI ASAS OPORTUNITAS DALAM PENUNTUTAN PADA MASA YANG AKAN DATANG - Rumapea, Mazmur Septian; Sutarajaya, I Wayan; Sudjana, I Ketut (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 02, Februari 2013, 2013)
The existence of the principle of opportunity in the prosecution in the future will increasingly have a broad understanding and inclusion of penal mediation as one of the provisions of the principle of opportunity to do by the prosecutor.
Keywords: Principle of Opportunity, Prosecution, Penal Mediation, Prosecutor